Pengaruh Manajemen Modal Kerja, Integrated Reporting dan Growth Opportunity terhadap Nilai Perusahaan: (Studi pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Arrasyi, Nurul Izzah; Wardoyo, Dwi Urip (eProceedings of Management, 2024)
The value of the company as a perception from investors of the company's performance. With a high company value,it can increase investors' confidence in the company's achievements and company projections. In line with thephenomenon discussed, namely the average company value and share price of companies in the food and beveragesub-sector listed on the Indonesia Stock Exchange in 2018-2022. The study was carried out to understand the impactof working capital management, integrated reporting and growth opportunities on company value simultaneously andpartially on the object of the study, namely food and beverage sub-sector companies listed on the Indonesia StockExchange in 2018-2022. This study uses a quantitative method with the sampling technique used, namely purposivesampling, with a sample of 16 companies in the food and beverage sub-sector that have IPOs for five years.Simultaneously it shows that working capital management, integrated reporting and growth opportunities show asignificance to the value of companies in the food and beverage sub-sector by 94%. Partially, the growth opportunityis significant positively to the company's value. In contrast, working capital management and integrated reporting arenot significant to the company's value. Keywords-working capital management; integrated reporting; growth opportunity; company value